Circular dichroism and Raman optical activity in antiferromagnetic transition metal fluorides - Hoffman, K.R.; Lockwood, D.J.; Yen, W.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
The Raman optical activity (ROA) of magnons in rutile-structure antiferromagnetic FeF2(TN = 78 K) has been studied as a function of temperature and applied magnetic field. For exciting light incident along the c axis, ROA is observed for magnons but not for phonons. In zero field, a small splitting (0.09 cm–1) of the two acoustic–magnon branches is observed for the first time by inelastic light scattering. The splitting in applied magnetic field is found to reduce with increasingtemperature in accordance with theory. No ROA was detected for two-magnon excitations. In optical absorption measurements performed over thirty years ago, a very small circular dichroism (CD) was observed in the magnon sidebands of other simple rutile antiferromagnetic fluorides (MnF2 and CoF2). The origin of this CD was not understood at the time. The Raman studies of the one-magnon Raman scattering in FeF2 have demonstrated that in zero field the degeneracy of the antiferromagnetic magnon branches is lifted by a weak magnetic dipole–dipole interaction, as predicted by Pincus and Loudon and by White four decades ago. The source of the observed CD in the magnon sidebands can now be traced to this same magnetic–dipole induced splitting.